2015
DOI: 10.1017/s0956536115000176
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic History, Ceramic Change, and Architectural Sequence at Acanmul, Campeche: A Local Chronicle and Its Regional Implications

Abstract: Acanmul is a medium-size center located at the north end of the Bay of Campeche about 25 km northeast of the city of Campeche. Between 1999 and 2005, three independent sets of investigations and major architectural consolidation were carried out at the center by archaeologists from the Universidad Autónoma de Campeche (UAC), the Instituto Nacional de Antropología e Historia (INAH), Centro Regional de Campeche, and UAC in collaboration with San Diego State University. These efforts produced a wealth of new info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(36 reference statements)
0
9
0
1
Order By: Relevance
“…Research by the Proyecto Champotón, directed by William Folan, and the CRSS, directed by the author, have documented a longer and more dynamic picture of regional settlement patterns (Ek 2012(Ek , 2015Folan et al 2003;Folan et al 2013;Forsyth 2013). These and other projects along the central Campeche coast have documented substantial Formative-and Classicperiod settlement (Ball and Taschek 2015;Ojeda 2010;Suárez et al 2010). The CRSS combined regional reconnaissance, intensive survey, and test excavations in the Río Champotón watershed to examine political, economic, and social change in the region (Figure 1).…”
Section: Recent Investigations In the Río Champotón Drainagementioning
confidence: 95%
See 3 more Smart Citations
“…Research by the Proyecto Champotón, directed by William Folan, and the CRSS, directed by the author, have documented a longer and more dynamic picture of regional settlement patterns (Ek 2012(Ek , 2015Folan et al 2003;Folan et al 2013;Forsyth 2013). These and other projects along the central Campeche coast have documented substantial Formative-and Classicperiod settlement (Ball and Taschek 2015;Ojeda 2010;Suárez et al 2010). The CRSS combined regional reconnaissance, intensive survey, and test excavations in the Río Champotón watershed to examine political, economic, and social change in the region (Figure 1).…”
Section: Recent Investigations In the Río Champotón Drainagementioning
confidence: 95%
“…The Champotón 4 ceramic complex is part of a regional ceramic sphere centered on Edzná and extending across west-central Campeche and the Chenes Region during the seventh and early eighth centuries (Ball and Taschek 2015;Benavides 1997:121-122;Forsyth 1983Forsyth :217, 2013Williams-Beck 1999). Although the preceding complex-Champotón 3-does not reflect participation in the material culture traditions of the interior Maya Lowlands (particularly the Tzakol sphere), Champotón 4 was a local expression of the Late Classic glossware ceramic tradition that developed in the interior southern Maya Lowlands.…”
Section: Champotón 4: the Three Kings Era (Ad 600-750)mentioning
confidence: 99%
See 2 more Smart Citations
“…In many of these reconstructions, primacy was placed with historical narratives of the movements of ethnic groups such as the Itza, and their role in larger scale pan-Mesoamerican cultural dynamics. Although later research on the iconography, architecture (Lincoln 1986), and ceramic chronologies (Ball 1979;Robles Castellanos 1990) of Chichen Itza clearly demonstrated that the division of chronologically distinct New and Old components was untenable, this framework for understanding the past proved quite durable (Folan 1991(Folan -1992.…”
Section: Historical Context: Changing Mesoamerican Interaction Spheresmentioning
confidence: 99%